Global Hotspots of Whale–Ship Collision Risk: A Multi-Species Framework Integrating Critical Habitat Zonation and Shipping Pressure for Conservation Prioritization - Bei Wang; Linlin Zhao; Tong Lu; Linjie Li; Tingting Li; Bailin Cong; Shenghao Liu (Animals)
The expansion of global maritime activities threatens marine ecosystems and biodiversity. Collisions between ships and marine megafauna profoundly impact vulnerable species such as whales, who serve as keystone predators. However, the specific regions most heavily affected by shipping traffic and the multi-species facing collision risk remain poorly understood. Here, we analyzed global shipping data to assess the distribution of areas with high shipping pressure and identify global hotspots for whale–ship collisions. The results reveal that high-pressure habitats are primarily distributed within exclusive economic zones (EEZs), which are generally consistent with the distribution of collision hotspots. High-pressure habitats exhibit significant spatial mismatch: 32.9% of Marine Protected Areas endure high shipping stress and yet occupy merely 1.25% of protected ocean area. Additionally, 25.1% of collision hotspots (top 1% risk) affect four or more whale species, forming critical aggregation in regions like the Gulf of St. Lawrence and Northeast Asian marginal seas. Most of these high-risk areas lack protective measures. These findings offer actionable spatial priorities for implementing targeted conservation strategies, such as the introduction of mandatory speed restrictions and dynamic vessel routing in high-risk, multi-species hotspots. By focusing on critical aggregation areas, these strategies will help mitigate whale mortality and enhance marine biodiversity protection, supporting the sustainable coexistence of maritime activities with vulnerable marine megafauna.